Growth factors IGF-1 and KGF and adipose-derived stem cells promote migration and viability of primary human keratinocytes in an in vitro wound model - Stadelmann, Nina; Horch, Raymund E.; Schmid, Rafael; Ostendorf, David; Peddi, Ajay; Promny, Theresa; Boos, Anja; Kengelbach-Weigand, Annika (Frontiers in Medicine, 2025)
Introduction: In the field of plastic surgery, epidermal transplantation is a potential treatment for chronic wounds that results in only minor donor site morbidity. Improving the regenerative capacities of epidermal grafts or single-cell suspensions and therefore accelerating healing processes would be of significant interest. Methods: In the present study, we analyzed the effects of growth factors and adipose-derived stem cells (ADSCs) on keratinocyte properties. For optimum translation into the clinical setting, primary human keratinocytes and patient-matched ADSCs were isolated and used in an in vitro wound model. Results: The keratinocyte migration and viability increased after treatment with the growth factors insulin-like growth factor 1 (IGF-1) and keratinocyte growth factor (KGF). A similar effect was observed with the use of a concentrated ADSC-conditioned medium (ADSC-CM). It was further possible to isolate the keratinocytes in a xenogen-free medium, which is essential for clinical translation. Importantly, a patient-dependent influence on the effects of the growth factors and ADSC-CM was observed. Discussion: This study provides potential for the improvement of epidermal transplantation in the treatment of chronic wounds using xenogen-free isolated and cultivated keratinocytes, growth factors, and ADSC. Translating these results into clinical application may help accelerate wound healing and shorten the time until patients can return to everyday life.
CRIS-Team Scopus Importer:2025-02-28
Keywords: adipose-derived stem cells; conditioned medium; growth factors; keratinocytes; wound healing